Technical Guidance on Making Meatballs Using Chicken Meat as the Basic Ingredient to Improve Students' Business Skills - Harapin Hafid; Asma Bio Kimestri; Siti Hadrayanti Ananda (Talenta Publisher Universitas Sumatera Utara, 2025)
As agents of change, community are required to acquire extensive knowledge and skills during their studies. The development of these skills should ideally be gained through practical activities during the academic process; however, this is often hindered by the lack of adequate facilities and infrastructure for practical training. This results in community not fully mastering the required skills. This science and technology application activity aims to strengthen the skills of animal science community through training in the production of meatball using chicken meat as the main ingredient. The activity was conducted at the Animal Science Department of the Faculty of Agriculture, Halu Oleo University. The methods used in the activity were as follows: (1) lectures and discussions on the potential and prospects of the bakso agroindustry and agribusiness, (2) demonstrations and guidance on meatball production, and (3) motivation for entrepreneurial spirit development. The results of the activity showed that the training materials presented received positive and satisfactory responses from the participants, as such activities had never been conducted before. Generally, the participants expressed interest in adopting the material on making baksos using chicken meat as the main ingredient. It was concluded that the target audience, consisting of animal science community, were enthusiastic and active in the technical guidance activities for meatball production. Overall, the training participants expressed a desire to engage in entrepreneurship by producing meatballs made from chicken meat.